FEATURES OF ACCOUNTING FOR INNOVATION PROCESSES AND RECOMMENDATIONS FOR ITS IMPROVEMENT (ResearchJet Journal of Analysis and Inventions, 2021)
This article highlights the importance of accounting in any enterprise in a market economy. It is important to pay attention to the importance of reports in the management and profitability of the enterprise and their correct, accurate and timely structure. One of the main drawbacks of the organization of accounting for innovation activities is that there is no unified system of accounts and accounting registers to reflect expenses, income and financial results of research activities.At the enterprise, the existing accounting registers and accounting accounts do not provide reliable data for the analysis of innovative products and their impact on the financial results of the enterprise.